Pengaruh Asam Salisilat Eksogen Terhadap Pertumbuhan dan Biomassa Tiga Kultivar Seledri (Apium graveolens L.) - Alviana Rochmania; Suratman; Solichatun (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This research aims to determine the effect of exogenous salicylic acid (SA) application at concentrations of 0 (control), 25, 50, 75, and 100 ppm on plant height, number of leaves, and fresh weight of three different celery cultivars, namely ‘Amigo’, ‘Aroma’, and ‘Summer green’. This study utilized a completely randomized factorial design. The first factor was the difference in celery cultivars, which consisted of three cultivars: ‘Amigo’, ‘Aroma’, and ‘Summer Green’. The second factor was the difference in salicylic acid concentration, which consisted of five levels: 0 ppm (control), 25 ppm, 50 ppm, 75 ppm, and 100 ppm. There were three replicates for each treatment. Plant height, number of leaves, and fresh weight were the parameters measured. A two-factorial analysis of variance (ANOVA) was used to analyze the data. The results of Duncan's Multiple Range Test at the 5% level showed that the results of the analysis were significant at less than 0.05. The results of the study showed that treatment with exogenous SA significantly affected the three celery cultivars. In general, the application of AS at lower concentrations (25 and 50 ppm) tended to increase growth parameters and biomass compared to the control. The 50 ppm AS treatment provided optimal results, especially in the ‘Summer green’ cultivar, which showed an increase in plant height, number of leaves, and fresh weight. Higher concentrations (75 and 100 ppm) showed negative effects, inhibiting growth and biomass, indicating toxicity. It can be concluded that the application of exogenous salicylic acid can be an effective strategy to increase celery productivity, provided that the his concentration is optimal. Differences in response between cultivars indicate the importance of determining the appropriate concentration for each plant type.